Corrosion resistance of AISI 304 and 444 stainless steel pipes in sanitizing solutions of clean-in-place process - Lins,Vanessa de Freitas Cunha (2016)
Stainless steel (SS) is successfully used in food industries due to the characteristics of its surface, which is essential for the maintenance of the properties of food. Tanks and stainless steel pipes, which come into direct contact with food and drink, undergo a process of cleaning and disinfecting called CIP (Clean-in-Place). This method consists of automatic recirculation of a detergent solution for a controlled time followed by a rinsing with water, and finally a cleaning and sanitizing solution immersion. This work consists of investigating the corrosion resistance of stainless steels used in the food industry using sanitizing solutions employed in the CIP procedure, and using electrochemical techniques such as potentiodynamic anodic polarization and electrochemical impedance spectroscopy.